Islamic mortgages: principles and practice. Issue 5 (1st August 2019) - Hanif, Muhammad
Abstract : Purpose: The purpose of this paper is to present an analysis of current practices of Islamic mortgages in the light of the principles of Islamic financial system, to document divergences – if any. A subsidiary goal is to develop an Islamic Mortgage Model (IMM) based on Musharakah principles. Design/methodology/approach: The author documents theoretical underpinnings of risk-return sharing from the Shari'ah perspective. A comparative study of conventional and Islamic mortgages is completed; existing practice of Islamic mortgages analyzed in the light of Musharakah principles and divergences identified. IMM is developed after taking divergences and Musharakah principles into considerations. A housing case is used to highlight differences (in financial terms) under multiple methods and scenarios. Findings: Study documents multiple divergences from Musharakah principles in the existing practice of Islamic mortgages including ignorance of market pricing in the negotiation of rentals and trading of equity units, and transfer of all ownership risks and rewards (vacancy, damage, destruction and market) to one partner (i.e. customer). Practice is divergent from principles in the area of economic substance. Modified IMM is developed by taking into account Musharakah principles; and differences highlighted by calculating financial figures – to determine financial rights and liabilities of the parties. Practical implications: Divergence from the principles of risk-return sharing leads to failure in the achievement of Islamic finance objective of equitable distribution of wealth. Moreover, protection of capital for financier reduces the market abilities to achieve financial stability by matching credit expansion with the rise in the real economy. Shari'ah boards and regulators, as well as, management of Islamic banking industry are expected to incorporate proposed changes in-practice for the realization of Islamic finance objectives. Originality/value: This study contributes to Islamic finance literature in the area of risk-return sharing. Based on important objectives of Islamic finance – equitable distribution of wealth and financial stability – divergences identified and a modified IMM in the light of Musharakah principles is presented. Descriptive rules are transformed into financial figures to document financial rights and liabilities of the concerned parties.